Reinventing batik stamping tool from recycle material / Mohd Rafizi Mohd Shari - Mohd Shari, Mohd Rafizi (2016)
In the history of Malaysian textile, Batik blok cloth has become an integral part in the Malay culture. This textile has long been established as daily attire for the commoners and has then remained an important traditional costume. However, many traditional motifs developed during the early years of the industry are disappearing unrecorded. The wood blocks with various authentic designs are found either eaten by termites or deteriorate due to weather condition. This research focuses on reinventing a new type of batik's block which retained its traditional motifs and also cost effective as to keep hold our traditional textile heritage. An experimental research was applied through 5 stages of processes that involved with recycled material obtained within the parameter. As a result, a plug-in or attached and detachable batik block with interrelated and refined patterns was established from a Sweetened Condensed Milk (SCM) aluminium can. This discovery will pave ways for more inventions of other types of recycled material that couldbe used through systematic and well-structured experiments/inventions.